An assessment of factors militating against enrollment of students in the field of business studies education in senior secondary schools in Katsina metropolis, Katsina State, Nigeria - Onaolapo, Oladapo; Onaolapo, Eniola (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2026)
Purpose: The paper assesses factors militating against students’ enrollment in the field of business studies education in senior secondary schools in Katsina Metropolis, Katsina State, Nigeria. Methodology: In the quest to obtain accurate data for the study, instrument for data collection was a structured closed ended questionnaire. The population of the studies was forty, which consists of nine examination officers, nine subject teachers and twenty-two SS1 students in total from nine selected senior secondary schools. A descriptive survey design was adopted for the study. The four (4) Likert’s rating instrument was used for easy elicitation of respondents’ opinions and subsequent analyzing of statistical data. Simple linear regression was used to test the null hypotheses at .05 significant level. Results and conclusion: Findings of the study revealed that students’ perception about business studies as a field of study, students’ self-efficacy and parent socioeconomic factors have significant influence on students’ enrollment in senior secondary schools. Implication of findings: The findings of this study have curriculum and policy implications, school and teacher implications as well as parental and community implications. Based on the findings, recommendations were made, among which is that schools should boost students’ awareness of career prospects in business studies by establishing business-related clubs, societies and competitions.